A facile amino-functionalization of poly(2-oxazoline)s' distal end through sequential azido end-capping and Staudinger reactions. (March 2017) - Osawa, Shigehito; Ishii, Takehiko; Takemoto, Hiroyasu; Osada, Kensuke; Kataoka, Kazunori
Graphical abstract: Highlights: Novel method to introduce primary-amino group into the distal chain end of POxs. Two step reactions to obtain POx-NH2 with 96% functionality in several hours. Applicable to one-pot reaction from Ox polymerization to amino end-functionalization. Capable of initiating NCA polymerization to obtain block copolymers. Abstract: Facile and quantitative method to introduce primary-amino group into the distal chain end of poly(2-substituted 2-oxazoline)s (POx)s, which have attracted progressive interest as platform polymers for various bio-functionality materials, was established here via two-step reactions; First, termination of cationic polymerization of 2-oxazoline using sodium azide as the end-capping reagent, followed by the conversion of the azido group to an amino group using triphenylphosphine (TPP) by the Staudinger reaction. The azido introduction step and the subsequent amino conversion step was accomplished within 1 h and 3 h, respectively, to ultimately obtain ω-amino-poly(2-ethyl-2-oxazoline) (PEtOx-NH2 ) with 96% functionality. The synthesized PEtOx-NH2 was subjected to ring-opening polymerization of N ε -trifluoroacetyl-l -lysine N -carboxy anhydride (Lys(TFA)-NCA) to successfully obtain the block copolymer PEtOx- b -PLys(TFA), which can be utilized as a platform polymer to develop polymer therapeutics, thus, demonstrating the versatility of the presently reported procedure for further functionalization of POx derivatives.